Policy Paradox : The Art Political Decision Making - Stone, Deborah (W.W. Norton & Company, 1998)
Unlike most texts, which treat policy analysis and policy making as different enterprises, Policy Paradox demonstrates that "you can’t take politics out of analysis." Through a uniquely rich and comprehensive model, this revised edition continues to show how real-world policy grows out of differing ideals, even definitions, of basic societal goals like security, equality, and liberty. The book also demonstrates how these ideals often conflict in policy implementation.